A Study on the Lateral Bearing Strength in Double and Quadruple Shear Joints of Populus deltoides - Pruthi, K. S.; Mamgain, A. K. (Indian Forester, 1994)
Results of tests conducted on structural joints made from Populus deltoides in three experimental series using diamond pointed common wire nails under variables of shear planes, inclination of grains to loading and the diameter are given in this paper. Safe loads for perpendicular to grain joints have generally been found lesser than those obtained for the joints loaded parallel to grain. Statistical analysis has shown that Elastic limit loads in respect of all the treatments do not differ significantly but displacement at this level indicates a trend that stiffness decreases with the increasing degree of inclination of grain to loading in the joints. The paper also includes safe working loads per nail, based on the confidential limits for use in design of permanent timber structures and the possible relationship between double and multiple shear strength of nails.